2021
DOI: 10.3390/jcdd8020012
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Histopathologic Evaluation of Type-A Aortic Dissections Implies a Uniform Multiple-Hit Causation

Abstract: (1) Background: The pathophysiologic basis of an acute type A aortic dissection (TAAD) is largely unknown. In an effort to evaluate vessel wall defects, we systematically studied aortic specimens in TAAD patients. (2) Methods: Ascending aortic wall specimens (n = 58, mean age 63 years) with TAAD were collected. Autopsy tissues (n = 17, mean age 63 years) served as controls. All sections were studied histopathologically. (3) Results: Pathomorphology in TAAD showed predominantly moderate elastic fiber fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Although several risk factors have been described predisposing individuals for this lethal condition, the exact pathogenesis has not yet been identified ( 18 ). Roughly, the development of an aortic dissection requires three main pathological conditions, being mechanical wall stress, a susceptible intimal layer and medial degeneration ( 12 , 19 ). Our previous study had shown that medial pathology in type A aortic dissections is comparable with thoracic aneurysms in patients with a tricuspid aortic valve with smooth muscle cell nuclei loss, mucoid extracellular matrix accumulation and elastic fiber fragmentation and loss ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several risk factors have been described predisposing individuals for this lethal condition, the exact pathogenesis has not yet been identified ( 18 ). Roughly, the development of an aortic dissection requires three main pathological conditions, being mechanical wall stress, a susceptible intimal layer and medial degeneration ( 12 , 19 ). Our previous study had shown that medial pathology in type A aortic dissections is comparable with thoracic aneurysms in patients with a tricuspid aortic valve with smooth muscle cell nuclei loss, mucoid extracellular matrix accumulation and elastic fiber fragmentation and loss ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Roughly, the development of an aortic dissection requires three main pathological conditions, being mechanical wall stress, a susceptible intimal layer and medial degeneration ( 12 , 19 ). Our previous study had shown that medial pathology in type A aortic dissections is comparable with thoracic aneurysms in patients with a tricuspid aortic valve with smooth muscle cell nuclei loss, mucoid extracellular matrix accumulation and elastic fiber fragmentation and loss ( 12 ). The intimal layer was, however, significantly thinner as compared to the tricuspid thoracic aortopathy patients, resembling the intima in patients with Marfan syndrome and a bicuspid aortic valve ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In specimens from patients with chronic aortic dilatation, the tenascin-C content in media was considerably lower and distributed more homogeneously around aortic media, whereas in healthy patients, tenascin-C was absent from the aortic specimens (71). Further, several histological studies have shown that dissection occurs most commonly in the outer third of the media layer in the area vascularized by the vasa vasorum network (72,73). In contrast, in patients with connective tissue disorder, the dissection is located closer to the aortic lumen in the middle third of aortic media (72).…”
Section: Dynamic Continuum Of Aortic Diseasementioning
confidence: 99%
“…An aortic dissection is a serious condition in which the inner layer of the aorta tears, blood surges through the tear, causing the inner and middle layers of the aorta to separate (dissect). 1 Based on their location and extent, an aortic dissection is classified as Stanford type-A aortic dissections (TAAD) (dissections involving the aortic root and/or ascending aorta, which can propagate to the aortic arch and further into the descending aorta), and type-B dissections (dissections that do not involve the ascending aorta). 2 …”
Section: Introductionmentioning
confidence: 99%